Inhibition of thyroid-stimulating hormone stimulation of protein kinase, glucose oxidation, and phospholipid synthesis in thyroid slices previously exposed to the hormone. - Field, J B; Bloom, G; Chou, C; Kerins, M E (The Journal of Clinical Investigation, 1977)
Prior exposure of thyroid slices to thyrotropin (TSH) induced refractoriness to subsequent stimulation of the cyclic AMP system by the hormone. Although the inhibition is incomplete, we examined whether the reduction in cyclic AMP was sufficient to alter other metabolic effects of TSH. Bovine or dog thyroid slices were incubated with or without 5-100 mU/ml TSH for 1-2h, washed, and then incubated without hormone for 1-2h. Half of the slices not exposed to TSH initially were then incubated with buffer and half were exposed to 5-100 mU/ml TSH. Slices initially incubated with TSH were also incubated with or without TSH in the third incubation. During the refractory period, TSH activation of protein kinase was inhibited even though the hormone still caused some increase in cyclic AMP concentrations. However, protein kinase activity was fully responsive to dibutyryl cyclic AMP when slices were incubated with it during the third incubation. Stimulation of glucose oxidation by TSH was significantly decreased in thyroid slices previously incubated with the hormone. During refractoriness, stimulation of glucose oxidation caused by prostaglandin E1 and dibutyryl cyclic AMP was also significantly diminished but that due to acetylcholine was not. Thus even though dibutyryl cyclic AMP could fully activate protein kinase activity during refractoriness, its effect on glucose oxidation was still inhibited, suggesting that the metabolic block responsible for this refractoriness was distal to activation of protein kinase. Stimulation of 32Pi incorporation into phospholipid by TSH and acetylcholine was also inhibited during refractoriness. Despite reduction of the stimulatory effect of TSH, binding of 125ITSH was not modified by prior incubation of thyroid slices with TSH. These results indicate that changes in the TSH receptor are not responsible for the development of refractoriness and other metabolic sites besides activation of adenylate cyclase appear to be involved.